2022
DOI: 10.31840/sya.vi25.2559
|View full text |Cite
|
Sign up to set email alerts
|

Distribución espacial de las áreas verdes urbanas en Xalapa, México: un caso de inequidad

Abstract: Las áreas verdes proporcionan beneficios y servicios ambientales y sociales a la población, sin embargo, generalmente, se distribuyen heterogéneamente en las ciudades, ligado a un aprovisionamiento desigual de tales beneficios, con implicaciones de justicia ambiental. Con base en un análisis cartográfico y estadístico, se evaluó la dotación y distribución espacial de las áreas verdes urbanas públicas en Xalapa, México, así como su relación con el Índice de Marginación Urbana del Consejo Nacional de Población. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Further research analyzing the relationship between LST, the presence and structure of green spaces and socioeconomic level of the population can help identify city areas with high need of heat mitigation intervention (Duncan et al, 2019). For Xalapa, it has been found that public urban green spaces show a clustered pattern, with no presence of these spaces in almost half of its neighborhoods, and that the lower number, surface, and percent of greens spaces were associated with areas of low socioeconomic level (Carmona-Ortega, 2021). Woefully, this is a common scenario in Mexican (Reyes-Plata and Gabriel-Bolea, 2018;Romo-Aguilar and de, 2008) and other Latin American cities (Gómez and Velázquez, 2018;Inostroza et al, 2016;Reyes-Päcke and Figueroa-Aldunce, 2010).…”
Section: Implications For Urban Planningmentioning
confidence: 99%
“…Further research analyzing the relationship between LST, the presence and structure of green spaces and socioeconomic level of the population can help identify city areas with high need of heat mitigation intervention (Duncan et al, 2019). For Xalapa, it has been found that public urban green spaces show a clustered pattern, with no presence of these spaces in almost half of its neighborhoods, and that the lower number, surface, and percent of greens spaces were associated with areas of low socioeconomic level (Carmona-Ortega, 2021). Woefully, this is a common scenario in Mexican (Reyes-Plata and Gabriel-Bolea, 2018;Romo-Aguilar and de, 2008) and other Latin American cities (Gómez and Velázquez, 2018;Inostroza et al, 2016;Reyes-Päcke and Figueroa-Aldunce, 2010).…”
Section: Implications For Urban Planningmentioning
confidence: 99%